Complimenting the Deep Ideas of Deutsch-Marletto Constructor Theory with the Computational Power of the Pythagorean-Plato Number System - Elnaschie, M. S. (European Journal of Applied Sciences, 2022)
Starting from the realization that constructor theory is an extension of David Deutsch’s quantum Turing machine while E-Infinity Cantorian space time is essentially a transfinite golden mean computer which is nearest to Alan Turing’s work, it follows inevitably that merging the deep ideas of Deutsch-Marletto with the computational power of E-Infinity theory would mean that the Pythagorean Platonic golden mean number system lies at the very root of physical science, art, philosophy and even consciousness. This has led to a truly great synthetic a priori as anticipated by the remarkable relatively recent constructor theory as well as the centuries old teachings of the acclaimed school of Alexandria. All these momentous conclusions were experimentally confirmed by the recent astounding discovery that gravity is of a quantum origin.